2013
DOI: 10.1177/2051013613480144
|View full text |Cite
|
Sign up to set email alerts
|

Working together: interactions between vaccine antigens and adjuvants

Abstract: The development of vaccines containing adjuvants has the potential to enhance antibody and cellular immune responses, broaden protective immunity against heterogeneous pathogen strains, enable antigen dose sparing, and facilitate efficacy in immunocompromised populations. Nevertheless, the structural interplay between antigen and adjuvant components is often not taken into account in the published literature. Interactions between antigen and adjuvant formulations should be well characterized to enable optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 101 publications
3
66
0
Order By: Relevance
“…28 Moreover, increased protein densities, which are apparent on the flattened liposomes, could alter cell uptake and immunogenicity due to multimeric antigen presentation. 29 Also it remains to be determined whether the presence of TLR agonists alters the formation of the flattened liposomes. Finally, the effects of different buffers and other common vaccine excipients on lipid structures should be evaluated.…”
mentioning
confidence: 99%
“…28 Moreover, increased protein densities, which are apparent on the flattened liposomes, could alter cell uptake and immunogenicity due to multimeric antigen presentation. 29 Also it remains to be determined whether the presence of TLR agonists alters the formation of the flattened liposomes. Finally, the effects of different buffers and other common vaccine excipients on lipid structures should be evaluated.…”
mentioning
confidence: 99%
“…This stimulated some studies into the conjugation of antigen to aluminium nanoparticles [97,98]. These studies showed that the aluminium particles are able to play the role of both carrier and adjuvant to stimulate the immune system, although it has also been shown that aluminium particles are capable of adsorbing antigen so tightly that antigen structure is altered, which reduces vaccine efficacy [98,99].…”
Section: Inorganic Particlesmentioning
confidence: 99%
“…Overall, it can be stated that proteins and peptides have improved the vaccine safety profile in comparison with live attenuated pathogens, however, their poor immunogenicity is definitely hindering their development and success (Gori et al, 2013;Purcell et al, 2007). For this reason, it is essential to advance in the design of novel adjuvants that may help providing these vaccines with a robust immune response (Fox et al, 2013).…”
Section: Peptidesmentioning
confidence: 99%